PENGEMBANGAN EKOSISTEM INDUSTRI KREATIF KULINER DENGAN MENGGUNAKAN HELIX MODEL (Kajian Sub Sektor Kuliner di Kota Bandar Lampung) - Umi Lestari; Arif Sugiono; Jeni Wulandari (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of the study was to describe the role of collaboration between actors in the development of the culinary creative industry in Bandar Lampung City. The problem is the lack of optimal cooperation between the actors involved. The theory uses General System Theory and Helix Model. This type of research is descriptive, qualitative approach. Data were collected through: interviews, observations and literature. Determination of informants with the purposive sampling. Data analysis by means of: data condensation, data verification and drawing conclusions. Data validation using source triangulation. From the research, it can be seen: (1) The development of the creative industry of Bandar Lampung City has involved academics, government, community, business, and mass media (2) Field findings are that academic actors have not developed optimally and (3) Cooperation between existing Penta helix model actors in Bandar Lampung City, from the results of the research, there has not been a collaboration synergy. Research recommendations: It is hoped that in the future the Government as a policy maker should maintain the business ecosystem through the preparation of long-term policy designs and programs and the next researcher is advised to take a research focus with a different locus or do a comparison with the same focus. Keywords: Collaboration, Ecosystem, Helix Model, Creative Industry, Culinary